Faktor Risiko Kejadian Gagal Ginjal Kronik Pada Usia Dewasa Muda Di Rsud Dr. Moewardi - UMI LATHIFAH, ANNIS; , Yuli Kusumawati, SKM., M. Kes (Epid); , Kusuma Estu Werdani, SKM, M.Kes (2016)
ABSTRACT Chronic renal failure was a progressive decline in renal function which ireveriabel when the kidneys are unable to maintain metabolic balance. The prevalence of kidney failure in Indonesia around 0.2%, while the prevalence of chronic renal failure in Central Java at 0.3%. The prevalence of young adults (0.3%) . The purpose of this study was to determine the risk factors for chronic renal failure in young adults in the Hospital Dr. Moewardi. This research method uses observational case control approach. The study population was patients with chronic renal failure young adulthood as many as 40 people. Selection of sample cases by way exhaustive sampling as many as 40 patients with chronic renal failure and selecting control samples with sample rendom sempling 40 patients with fractures. The statistical test using chi squarei with the help of statistical software. The results showed no relationship between diabetes mellitus ( p = 0.001 OR = 31.909 95% CI = 3.985 to 255.513) hypertension ( p = 0.001 OR = 152.111 95% CI = 28.809 to 803,139) and a supplement drink consumption ( p = 0.001 OR = 8.037 95% CI = 2.945 to 21.935) and the incidence of chronic renal failure in hospitals Dr. Moewardi.